The Effect of the Japan 2011 Disaster on Nuclear and Alternative Energy Stocks Worldwide: An Event Study - Robert Ferstl; Sebastian Utz; Maximilian Wimmer (BuR - Business Research, 2012)
This event study investigates the impact of the Japanese nuclear disaster in Fukushima-Daiichi on the daily stock prices of French, German, Japanese, and U.S. nuclear utility and alternative energy firms. Hypotheses regarding the (cumulative) abnormal returns based on a three-factor model are analyzed through joint tests by multivariate regression models and bootstrapping. Our results show significant abnormal returns for Japanese nuclear utility firms during the one-week event window and the subsequent four-week post-event window. Furthermore, while French and German nuclear utility and alternative energy stocks exhibit significant abnormal returns during the event window, we cannot confirm abnormal returns for U.S. stocks.
urn:nbn:de:0009-20-33091
Keywords: 650; Fama-French model; Fukushima-Daiichi; bootstrap; event study; nuclear accidents; Börsenkurs; Deutsch; Französisch; Japanisch; Kernkraftwerk; Störfall; Erneuerbare Energie; Event Study; Japan